Cambodian rice farmers’ knowledge, attitudes, and practices (KAPs) regarding insect pest management and pesticide use - Lucinda Dunn; Tanya Latty; Floris F. Van Ogtrop; Daniel K.Y. Tan (International Journal of Agricultural Sustainability, 2023)
Insect pests are a serious problem for rice farmers in Cambodia, threatening livelihoods and food security. To protect their yields, farmers are dependent on broad-spectrum pesticides, which has led to a pesticide ‘lock-in’ scenario. Our study aimed to better understand farmers’ current pest management practices and the underlying knowledge and attitudes driving these behaviours. We surveyed rice farming households (n = 168) from five different villages in Battambang Province, Cambodia. Survey respondents considered insect pests to be the most significant cause of yield loss. Respondents depended solely on chemical insecticides to manage insect pests. Combinations of agronomic and pesticide application practices contributed to pesticide dependency, including high seeding rate, insecticide timing and application rate. Additionally, 77% of respondents misidentified the beneficial lady beetle, Micraspis discolor, as a pest. Respondents indicated a desire for education and training on pest and beneficial arthropod identification, safe pesticide use, and improved cropping practices. We suggest critical areas for education and training are damage thresholds of local pests, the role of natural enemies, and improved awareness of pesticide toxicity and exposure. Promoting local knowledge sharing to engage and empower farmers to make informed decisions about their own pest management can forge a pathway away from pesticide dependency.